Differences in Blood Pressure and Obesity According to the Physical Fitness Level for Korean Older Persons: Considering Data from the National Fitness 100 - BongJu Sung; JiWon Seo; JeongYeol Lee (Korea Institute of Sport Science, 2022)
PURPOSE High blood pressure and obesity pose significant health problems for older individuals. Previous studies showed that regular exercise improves physical fitness factors and decreases blood pressure and obesity. Therefore, this study investigated differences in blood pressure and obesity according to the physical fitness level of Korean older individuals using the National Fitness 100 data and used them to recognize the importance of maintaining physical fitness through regular physical activity or exercise for older individuals. METHODS From 2013 to 2019, a total of 218,848 subjects (men=74,271, women=144,577) aged ≥65 years who participated in the National Fitness 100 had their muscular strength, muscular endurance, cardiorespiratory endurance, balance, coordination, and flexibility measured, and they were ascribed a fitness level. Blood pressure, body mass index (BMI), percentage of bodyfat, and waist circumference were measured to compare the difference in fitness level. RESULTS There was a significant difference in the systolic and diastolic blood pressure in older men, and the diastolic blood pressure of older women by the fitness level (p<.001). In both older men and women, there was a significant difference in BMI, percentage of bodyfat, and waist circumference according to the fitness level (p<.001). CONCLUSIONS In conclusion, men and women showed different aspects in blood pressure, but Korean older individuals with having a high level of fitness managed their weight and body fat well. The decrease in obesity and improvement of physical fitness through regular physical activity and exercise could be a positive effect on maintaining health and extending healthy life years.